Pengaruh Metode Pembuatan yang Berbeda terhadap Mutu Sensoris Roti Bluder - Felicia Andriani; Cucu Cahyana; Ridawati Ridawati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This research aims to identify the effect of different manufacturing methods on the sensory quality of bloeder bread. The method used is experimental. This research was conducted at Jakarta State University with a sample of 45 Culinary Education students who were somewhat trained panelists. Based on the Kruskal Wallis test, it can be concluded that there is an influence of different methods of making bloeder bread on the volume and crust aspects of the bread. Meanwhile, there was no real influence on aspects of upper skin color, skin characteristics, aroma, crumb pores, crumb color, crumb texture, taste and chewing quality.